2012
DOI: 10.1002/ptr.4824
|View full text |Cite
|
Sign up to set email alerts
|

The Immunosuppressive Activity of Pseudolaric Acid B on T lymphocytes in vitro

Abstract: Pseudolaric acid B (PB) is a major bioactive component extracted from Pseudolarix kaempferi. Traditional medicine practitioners in China have been using the roots of this plant to treat inflammatory and microbial dermatoses for centuries. In this study, the experiments were conducted to investigate immunosuppressive activity of PB on T lymphocytes in vitro. The results show that PB has hypotoxicity on hepatocytes and renal cells assessed by Methyl thiazolyl tetrazoliym (MTT) Assay and selectively inhibits the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…It has been reported that PAB could inhibit mitogen and alloantigen-induced T cell proliferation and activation (Li et al, 2009;Wei et al, 2013). In the present study, we further measured the activity of HPAB on T cell proliferation in vitro.…”
Section: Hpab Inhibits T Cell Proliferation Without Obvious Cytotoxicmentioning
confidence: 93%
See 4 more Smart Citations
“…It has been reported that PAB could inhibit mitogen and alloantigen-induced T cell proliferation and activation (Li et al, 2009;Wei et al, 2013). In the present study, we further measured the activity of HPAB on T cell proliferation in vitro.…”
Section: Hpab Inhibits T Cell Proliferation Without Obvious Cytotoxicmentioning
confidence: 93%
“…Mixed-leukocyte reaction (MLR) assay was used to assess the effect of HPAB on T cell proliferation induced by alloantigen (Wei et al, 2013). Briefly, C57BL/6 splenic lymphocytes (stimulator cells)…”
Section: T Cell Proliferation Assaymentioning
confidence: 99%
See 3 more Smart Citations